2014
DOI: 10.1039/c3nj01334k
|View full text |Cite
|
Sign up to set email alerts
|

Silver-promoted gelation studies of an unorthodox chelating tripodal pyridine–pyrazole-based ligand: templated growth of catalytic silver nanoparticles, gas and dye adsorption

Abstract: A novel tripodal pyridine-pyrazole based tris amide ligand, namely, N 1 ,N 3 ,N 5 -tris(3-(pyridin-2-yl)-1Hpyrazol-5-yl)benzene-1,3,5-tricarboxamide was synthesized. The ligand acts as a promising low molecular weight gelator that gels silver salts in presence of water. The gels formed were found to be highly stable to heat and stress. Moreover, silver ions not only act as a gelling agent but also participate in nanoparticulate formation. The three-dimensional ligand-silver gel matrix serves as an excellent pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In another article, the authors also reported the ability of these gelators to respond to the presence of silver salts in water. 78 Coordination of the metal ions with the pyridine-pyrazole was responsible for metallogel formation. Furthermore, the ligand transformed Ag + ions into Ag nanoparticles.…”
Section: Supramolecular Gels For Heavy Metal Uptake From Watermentioning
confidence: 99%
“…In another article, the authors also reported the ability of these gelators to respond to the presence of silver salts in water. 78 Coordination of the metal ions with the pyridine-pyrazole was responsible for metallogel formation. Furthermore, the ligand transformed Ag + ions into Ag nanoparticles.…”
Section: Supramolecular Gels For Heavy Metal Uptake From Watermentioning
confidence: 99%
“…32 However, most modications only changed the chitosan-active groups, not its original structures. 33 Recently, through the design of 3D porous structures in some natural materials, excellent properties have been found, including catalysis, adsorption and electrochemical activities. [34][35][36] The 3D porous structures not only reduce the original density of the material but also improve the exposure and accessibility of active sites to the target, 37,38 which should be very useful for adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Among all kinds of approaches, absorption is more preferred due to its low cost, high efficiency, and easy handling. Supramolecular hydrogels which contain both hydrophilic and hydrophobic groups can absorb a variety of dyes [ 98 ] and may have advantage in the recycle and adsorption rate.…”
Section: Hydrogelsmentioning
confidence: 99%